ADVANTAGES OF THE DRUG HEPTRAL - Axmedov Shamshod Jamshidovich; Ergashov Bekhruzjon Komilovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Chronic hepatitis C virus (HCV) is one of the most serious medical problems worldwide. The hepatitis C virus is not only the main etiologic factor of liver disease, but also causes the development of extrahepatic manifestations [10], the clinic of which often comes to the forefront, becomes the cause of disability of patients and reduced quality of life [2].